Strategi Pemasaran Dalam Pengembangan UMKM Melalui Digital Marketing (Studi Kasus UMKM Dapur Mommy, Kelurahan Rembang, Kecamatan Sananwetan, Kota Blitar) - Salsabilla Prabawati Hariyono; Jojok Dwiridotjahjono (Universitas Katolik Widya Karya Malang, 2023)
In this day and age, people of all ages are very familiar with digital technology. The right application of digital technology can provide benefits for its users. One of them is by creating marketing for business products and services organized by UMKM using digital technology. However, due to a lack of understanding and training, UMKM business owners have not made the best use of the internet to assist their operations. Digital marketing, which aims to advertise or promote products and services using online media to reach a larger target market, is one way to use the internet in company management. Foodstuffs are the only goods produced by UMKM owned by business actors in Rembang Village and marketing is only carried out through direct sales by door to door or face to face. It is difficult to reach a larger target market. Therefore, providing training and directing the use of digital marketing can help MSME players in increasing the capacity of UMKM entrepreneurs to utilize digital marketing.